2008
DOI: 10.3200/jach.56.5.499-504
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic Androgenic Steroids: Use and Perceived Use in Nonathlete College Students

Abstract: Anabolic androgenic steroids (AAS) are used not only for the enhancement of athletic prowess, but also for promoting a muscular appearance -traits that may be appealing to many non-athlete college students. Purpose: This study investigated the use and perceived use of AAS among non-athlete college students. Methods: A survey on use and perceived use of AAS was administered to a cross section of non-athlete students at a major metropolitan university. Results:Of the 485 non-athlete college students participatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Alaranta et al (2006) indicates that there are differences between sports in their attitude to doping. Yet, even though this difference exists, much of the existing research has mixed competitive athlete and amateur or non-athlete populations within their samples (for example, Berning et al, 2008; Dunn et al, 2009; Laure et al, 2005; Matich, 2007; Parkinson and Evans, 2006; Perry et al, 2005). In addition, the survey methods used to obtain data on attitudes and use of PEDs have been called into question by a number of authors (Alaranta et al, 2006; Judge et al, 2010; Pope et al, 1988).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Alaranta et al (2006) indicates that there are differences between sports in their attitude to doping. Yet, even though this difference exists, much of the existing research has mixed competitive athlete and amateur or non-athlete populations within their samples (for example, Berning et al, 2008; Dunn et al, 2009; Laure et al, 2005; Matich, 2007; Parkinson and Evans, 2006; Perry et al, 2005). In addition, the survey methods used to obtain data on attitudes and use of PEDs have been called into question by a number of authors (Alaranta et al, 2006; Judge et al, 2010; Pope et al, 1988).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Recent research suggests that AAS use has now extended beyond professional athletes to adolescents, college students and females (Berning et al, 2008; McCabe et al, 2007; U.S Department of Health and Human Services, 2007; van den Berg et al, 2007). AAS and exercise have a strong link, because anabolic gains are maximized through the combination of AAS with exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Data from the Youth Risk Behavior Survey suggests 4.6% of 12th-grade males and 1.6% of 12th-grade females have taken steroid shots or pills without a doctor's prescription (Eaton, Kann, Kinchen et al, 2010). Berning et al (2008) recently surveyed 485 students at a major metropolitan university and found that 9% had previously used anabolic steroids. Seniors were the most likely users while freshman were least likely.…”
mentioning
confidence: 99%